BBS News Vol.9(2) (Bangladesh Journal of Bioethics, 2018)
20th Asian Bioethics Conference (ABC20) will be held on 22-25 Nov, 2019 at Dhaka, Bangladesh, organized by Bangladesh Bioethics Society (BBS) and  in the cooperation with DGHS, Ministry of Health and Family welfare, People Republic of Bangladesh and in conjunction with ABA and Eubios Ethics Institute, Thailand, New Zeeland’s and Japan. It provides opportunity for all scholars around the world to gather feedback on their research, maximize networking opportunities, and learn the latest news and information and methodologies on bioethics. It is our great honor to welcome you to the ABC20 at Dhaka, Bangladesh.Bangladesh Bioethics Society (BBS) is the pioneer in bioethics, has been promoting integrity for sustainable development of Bangladesh since the beginning of 21st century. These actions reflect the nation’s effort as a member of the global community in developing science and biotechnology as well as in societal reform for protecting civil rights in ethical, legal, and social senses. The conference brings together scholars and policy makers from many disciplines all around the world (beyond just Asia and the Pacific) to discuss and deliberate on the latest issues facing humanity.The previous conferences was held in China, Japan, Korea, Turkey, Thailand, Malaysia, Indonesia, India, Iran, the Philippines and Taiwan.Please view at http://www.abc20.bioethics.org.bd/index.html